Development of methodologies to quantify metal-based heat generation - Maestre-Cambronel, Daniel (My University, 2025)
Decarbonizing residential heating requires the widespread implementation of cleaner energy infrastructures. The absence of reliable technologies to phase out natural gas (NG) from communities remains a key barrier to arresting residential emissions. In Ontario, most of the residential heating demand is supplied by NG since it supports energy security and affordability. However, the extensive emissions associated with its combustion pose increased concern for global warming. This thesis investigates the development of a methodology to quantify municipal metal resources to meet residential heating demands while assessing its impact on reducing Greenhouse Gas (GHG) emissions. The technology that enables heat production from hard-to-recycle metals is metal-water reactions (MWR), which produce hydrogen and heat on demand. For the analysis, comprehensive geospatial quantification of non-ferrous metals stocks will be derived in Ontario communities from (1) municipal solid waste (MSW) and (2) end-of-life automotive vehicles. This is expected to unravel the availability of previously discarded metals for heat production in various geographical contexts and time frames. The methodology provides reproducible steps to replicate the analysis in multiple contexts, facilitating community energy planning. It also offers a novel integration of open-source waste management data, socio-economic parameters, machine learning and energy modelling that extends flexible implementation and can be tailored in the future to improve predictive capabilities. The outcome of this investigation is expected to benefit community energy planning, as it creates a framework to accurately quantify and forecast community resources, empowering communities to make informed decisions about the suitability and potential of metal-based energy infrastructure. The results showed that the targeted communities in Ontario (Hamilton, Peel and Halton) can produce between 10 and 33 GWh of clean heat by 2050 from MSW resources. The clean heat generation potential from the automotive sector is estimated to be up to 5.7 GWh per year, representing an overall reduction of up to 1 ktonnes of CO2 from residential heating. Metal-based heat generation at the Ontario level can reduce up to 3% of the residential heat demand compared to the 2019 baseline. The same community resources can reduce heat demand by up to 33% in remote regions.
Master thesis
Keywords: Metal-based heat generation; Hydrogen technologies; Decarbonization of residential heating; Municipal solid waste; Metal-water reactions; Waste management